Advertising and promotional campaign for H&R Johnson (Malaysia) Sdn. Bhd. / Ahmad Nasir Yaacob - Yaacob, Ahmad Nasir (1992)
The area of the study are specific to the present advertising and promotional activities at H & R Johnson. The aim of this study is to determine the effectiveness of the advertising and promotional campaign in the H & R Johnson.